PENGARUH ANALISIS FUNDAMENTAL TERHADAP RETURN SAHAM, ANALISA KOMPARASI PERBANDINGAN BANK PADA BANK UMUM KEGIATAN USAHA (BUKU) 3-4 DAN BUKU 1-2 DI INDONESIA - Ariza Viska Ramadhan,; Fajri Adrianto (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
This study aims to determine and analyze the effect of fundamental analysis on stock returns in Commercial Banks Business Activities (BOOK) 3 4 and BOOK 1 2 in Indonesia. This research is a causative study with quantitative methods. The sampling technique is done by purposive sampling method with a total sample of 18 BOOKS. This study uses panel data regression analysis with the standard program version 12.00. The results showed that return on equity (ROE), price book value (PBV), and capital adequacy ratio (CAR) had a significant effect on stock returns in BOOK 1 2, while in BOOK 3 4 the variables that significantly affected stock returns were earnings per share ( EPS).Keywords: Return On Assets (ROA), Return On Equity (ROE), Price Book Value (PBV), Price to Earning Ratio (PER), Earning Per Share (EPS), Devidend Per Share (DPS), Capital Adequacy Ratio ( CAR), and Stock Return